Eksistensi Keilmuan Islam - Nurdin, Nurdin (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2013)
Material objects of Islamic knowladge is not limited to the subject - matter that is empirical, but also the metaphysical .The Islamic sciences are classified into basic groups and groups of branches of these two groups were divided into the Islamic sciences fields. These areas are the fields ; the source of the teachings of Islam, in Islamic thought, social institutions, and the history of Islamic civilization, language and literature of Islam, Islamic education, propagation of Islam and the modern development/renewal in the fields. Classification of the Islamic sciences does contain ambiguity of settings in addition to the lack of clarity reason why only eight fields. From the classification of the Islamic sciences, one group can be classified again into the thicket human sciences, while another group can be classified into clumps social sciences and the sciences of nature (natural). Both clumps Islamic sciences (humanities and social sciences) have in common in terms of information elements and element methodology.